Fendas Orofaciais : estudo farmacoepidemiológico e o papel do ácido fólico - Figueiredo, Rita de Cássia Feguri (2011)
The use of folate in preventing birth defects including OFCs (orofacial clefts) is a path that for many decades until the present day, by several researchers, in seeking to correlate the possible relationships between exposure and genetic susceptibility to environmental variables influencing or determining directly or indirectly the development of malformations such as OFC, discussing experimental and epidemiological evidence for a possible role of folate in prevention. Objectives. Evaluate data collected through entrevistaem women of reproductive age with folate supplementation and the possible influence of diet as a factor preventing OFCs and importance of these and other environmental variables in the development of this malformation, checking the possible associations involved in homocysteine metabolism providing the potential for birth defects. Methods. We used an observational cross-sectional study if the primary control.Were collected from mothers of patients with OFCs composed of individuals of both sexes treated at the Hospital Universitário Júlio Müller (HUJM) and the Hospital Geral Universitario (HGU) in Cuiabá - MT, information of the mothers during the regular period, pregnancy and pre pregnancy through a standardized interview, a total sample of 61 patients to identify socio-demographic, epidemiological, health care in which they interviewed experienced at different times of life when they sought a facility located within the state of MT. Results. There was a low folate intake by mothers, especially in the affected group (p<0,05). The orientation and prevention with folate supplementation was very poor in the whole sample, being non-existent in both groups of reproductive age, and significantly lower in the case group compared with the control in the peri-conception, that is, three months before of gestation and the first trimester (p<0.05). There was also a failure of family planning in both groups. The 2D US (twodimensional ultrasound) showed a low sensitivity of prenatal diagnosis of OFCs during pregnancy, birth and the examination showed low efficacy in the diagnosis of isolated cleft palate. Conclusions. Through epidemiological studies conducted in this thesis, we observed limited family planning, a diet low in folate by womeninterviewed, and a deficiency of guidance and prevention of congenital anomalies like OFC with the use of folate in women reproductive period and peri-conception. The diagnosys of OFCs also seemed very poor, both during pregnancy with the use of 2D US, as at birth. Thus, it was evident the need to improve prevention and diagnosis of OFCs with better qualification of the professionals involved and health awareness in the community in general.